STRESS LEVEL ANALYSIS IN MEDICAL FACULTY ONLINE LEARNING IN SURABAYA - Winnie Nirmala Santosa; Anita Dahliana; Shang Rani Ayom Lyberta Ar Raniri; Ida Bagus Made Artadana (Fakultas Kedokteran Universitas Alkhairaat, 2024)
Every nation must move swiftly to stop the COVID-19 virus from spreading because of its rapid dissemination. This includes altering learning models. Some students experience stress when switching from traditional classroom models to online learning, which makes it difficult for them to fully engage in the teaching and learning process. A study was done to find out how stressed out students in the University of Surabaya's Faculty of Medicine from the 2017 to 2020 class were about their online coursework. This study uses a cross-sectional research design and is a component of an analytical observational study. In this study, students' stress levels at the University of Surabaya's Faculty of Medicine were assessed using questionnaire data from the online learning model. The chi-square test and the Slovin formula are used to calculate the sample size once the data has been collected and processed using the SPSS version 22 program. Chi square investigation revealed that the significance between the two was 0.350, indicating that there is no association between them. Based on the available information, it was discovered that 58% of participants fell into the normal stress category, and 2% fell into the really severe stress category. Stress from online model learning is not significantly correlated with students at the Surabaya Faculty of Medicine. This is possible because students can adjust to online learning well and because individual variances in coping methods can also contribute to variations in the amount of academic stress that students experience.